Relevance of zeta potential as a tool for predicting the response of controlled salinity waterflooding in oil–water-carbonate systems. (15th September 2022) - Rodrigues, Romain; Levant, Michael; Klimenko, Alexandra
Highlights: Comparison of streaming potential at Sw = 1 and Sor is more complicated than expected. Many inconsistencies between streaming potential and electrophoretic mobility measurements for oil/water interface have been observed. Both methods may have important limitations in determining representative values of zeta potential. Zeta potential can only capture a few steps of the entire oil recovery process. Abstract: Zeta potential has been proposed as a key parameter for predicting the response of controlled salinity waterflooding, as correlation with additional oil recovery has previously been established. However, it is unclear if there is a causal effect and if this parameter can be used as a unique predictive tool. We provide new insights with a detailed investigation into the role of the change of polarities of oil/water/rock interfaces on the additional oil recovery. Core flooding experiments with streaming potential and electrophoretic mobility measurements were performed to obtain insights into the electrostatic interactions that occur during oil recovery on Estaillades rock. Two different injection scenarios were followed in one crude oil/brine/rock (COBR) system: one conventional injection with decreasing salinity and one inverse injection with increasing salinity. Results indicated that oil recovery in secondary mode was more important using formation brine compared to low salinity brine. Also, almost no additional oil recovery was observed in tertiary mode irrespective of the injection scenario. Rock/water zeta potential was found positive in formation brine, and negative in the low salinity brines. The determination of oil/water polarity was more difficult as many inconsistencies between streaming potential and electrophoretic mobility measurements were observed. We propose several explanations for these discrepancies, including that the difference in zeta potential at fully water saturation and at residual saturation is not necessarily dependent on oil polarity as it can be induced by a change in rock exposed surface and in the distribution in water flow paths during measurements. The overall results suggest that zeta potential cannot be used as a unique indicator to predict the low salinity response of a COBR system.